Analisis Keterlaksanaan Pembelajaran Berdiferensiasi Pada Pembelajaran Matematika (Studi Kasus: Kelas 10 SMA Negeri di Bangkinang Kota) - Anneke De Resta (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the challenges faced by teachers in implementing differentiated instruction in mathematics lessons in the XII IPS class at SMA Negeri Bangkinang Kota. Differentiated instruction is an approach tailored to students' needs, interests, and abilities, allowing each student to learn according to their own pace and learning style. The findings of the study indicate that the main challenges in implementing differentiated instruction include teachers' limited understanding of the concept, constraints of time and resources, and students' insufficient foundational knowledge in mathematics. Teachers also face difficulties in effectively mapping students' needs, which hinders the success of differentiated instruction. The solutions proposed include increasing the availability and utilization of diverse learning materials, using technology to support more interactive learning, extending planning and implementation time, and providing training for teachers to enhance their competency in designing differentiated lessons. Additionally, collaboration between teachers, school principals, and relevant stakeholders is necessary to provide adequate resources and infrastructure. With the implementation of these solutions, it is expected that differentiated instruction can be carried out more effectively and optimally, leading to improved student learning outcomes in mathematics classes.